The application of normative performance profiling for talent Identification in youth association football - Delves, A.; Robins, M. T. (World Congress of Performance Analysis of Sport IX, 2012)
Talent identification is the process by which an individual is selected based upon judgements made about their future performance potential. Traditionally, professional football clubs rely on the subjective judgements of scouts or coaches when assessing players (see Williams and Reilly, 2000), but Costa et al. (2010) have suggested that when selecting and identifying players for future development, skill assessments such as technical components should be emphasised, with a lesser degree of importance placed on physical attributes. One approach that could provide invaluable technical performance insights is the normative performance profiling technique (O`Donoghue, 2005). Prozone Match-Insight (Prozone Sports Ltd, Leeds, UK) was used to analyse all thirty matches from the 2009/2010 season of a professional football club`s U18 academy side. Key position-specific performance indicators (KPI`s) were selected for each individual player and cross-validated with the team`s coach. Normative performance profiles were then created for each player using the technique proposed by O`Donoghue (2005). Briefly, this entailed comparing the mean, upper quartile and lower quartile for each of the individual player`s KPI`s against the normative data derived from opponents of the same position. The results of the current study (Figures 1 and 2) demonstrate the utility of normative performance profiling for talent identification. Normative profiling allows strengths and weaknesses of players to be identified and KPI`s to be directly compared to players from the same position. Used in conjunction with traditional maturational factors, analysis of technical performance using such a profiling technique would provide a more holistic account of player potential and more appropriately inform talent identification processes.